2017
DOI: 10.18699/vj17.317
|View full text |Cite
|
Sign up to set email alerts
|

Parasites of the genus Nosema, Crithidia and Lotmaria in the honeybee and bumblebee populations: a case study in India

Abstract: 1 Федеральный исследовательский центр Институт цитологии и генетики Сибирского отделения Российской академии наук, Новосибирск, Россия 2 Новосибирский национальный исследовательский государственный университет, Новосибирск, Россия 3 Институт биологии, экологии и природных ресурсов, Кемеровский государственный университет, Кемерово, Россия 4 Институт наук об окружающей среде, Ягеллонский университет, Краков, Польша 5 Институт систематики и экологии животных Сибирского отделения Российской академии наук, Новосиб… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Recently, a novel trypanosomatid parasite was discovered and named L. passim 7 . L. passim seems to be more prevalent than C. mellificae [7][8][9][10][11][12][13][14][15][16][17][18] . Although the association of L. passim infection with winter mortality of honey bee colonies was suggested in several studies 19,20 , the effects of L. passim infection on honey bee health and colony survival remain poorly understood.…”
mentioning
confidence: 95%
“…Recently, a novel trypanosomatid parasite was discovered and named L. passim 7 . L. passim seems to be more prevalent than C. mellificae [7][8][9][10][11][12][13][14][15][16][17][18] . Although the association of L. passim infection with winter mortality of honey bee colonies was suggested in several studies 19,20 , the effects of L. passim infection on honey bee health and colony survival remain poorly understood.…”
mentioning
confidence: 95%
“…Later, in 2015, another novel trypanosomatid parasite infecting honey bees was discovered and named L. passim (Schwarz et al, 2015). L. passim was found to be more prevalent than C. mellificae (Schmid-Hempel and Tognazzo, 2010; Morimoto et al, 2013; Cepero et al, 2014; Ravoet et al, 2014, 2015; Cersini et al, 2015; Schwarz et al, 2015; Arismendi et al, 2016; Cavigli et al, 2016; Stevanovic et al, 2016; Vavilova et al, 2017; Regan et al, 2018) and fewer honey bee colonies were reported to be infected by C. mellificae (Ravoet et al, 2015). Thus, L. passim rather than C. mellificae is likely to be associated with the previously reported winter mortality of honey bee colonies (Ravoet et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Apis D,N X [16,18,28,29,30,31,32,33,34,35,36,37,38,39,40,41] (5) X [43] (>1) X [4,13,16,18,29,30,31,32,33,35,36,37,40,41,43,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67] (>10)…”
Section: Host Genera Nosema Apis Nosema Bombi Nosema Ceranaementioning
confidence: 99%